Exploring Afrocentric themes and illustrations in South African children’s literature with human characters from 2010-2020 - Tshuma, Sibusiso (My University, 2021)
The principal objective of this research is to explore thematic concerns raised in Afrocentric children’s literature and how illustrations are used in the making of such books. The research explored how general children’s themes are presented in an Afrocentric way to make the children’s books Afrocentric to cater to the African child’s values. This research is concerned primarily with themes of Afrocentricity in its broader sense which mainly look at social, political, racial and cultural identities as portrayed in children’s literature. The central goal of the discussion is to show how these texts reflect an African perspective on African children. It is in this context that the research examines the ideological foundations of Afrocentrism as developed by Asante as it attempts to provide a framework for exploring societal, sociological, cultural and political problems of the black children in South Africa, post-apartheid as outlined in selected texts. Afrocentric children’s literature will loosely mean children’s literature written for African children, by a South African author regardless of race provided its narrative is centred on the African child. The research therefore analyses how general themes of Afrocentricity have been incorporated into post-apartheid South African children’s books that feature human characters. This was achieved through triangulation of three forms of qualitative data: interviews, textual analysis and foregrounding the study on the Afrocentric theoretical framework. The findings show that use of Afrocentric themes is centred on rewriting the history, politics, social relations, religion and culture of the black people in the best interest of African children. African values were consistently present in the selected texts with more elaborate and dignified closer to life illustrations of the black child. The study recommended that there is need for production of more of such books and that these should be made available and easily accessible
A research report submitted to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Arts in Publishing Studies, 2021